Pengaruh Lingkungan Keluarga dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha Siswa SMK Negeri 1 Baradatu Kabupaten Way Kanan - Rina Loliyana; Rini Loliyani; Kevin Alando (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to determine the effect of the Family Environment and Entrepreneurship Education on the Entrepreneurial Interests of students at SMK Negeri 1 Baradatu, Way Kanan Regency. The type of data in this study uses quantitative research using primary and secondary data. In this study using probability sampling technique to determine the research sample because it has a population of over 100, the determination of the research sample using the slovin formula obtained results of 77.42 rounded up to 77 respondents. The analysis technique used is through validity, reliability, classic assumptions, hypotheses. From the results of the research that has been done, it shows that the Family Environment and Entrepreneurship Education have a significant joint effect on the Interest in Entrepreneurship of grade 1 and 2 students of SMK Negeri 1 Baradatu, Way Kanan Regency. Family Environment and Entrepreneurship Education have an effect of 68.0% on Interest in Entrepreneurship of grade 1 and 2 students of SMK Negeri 1 Baradatu, Way Kanan Regency. While the remaining 32.0% is influenced by other factors not examined in this study.